2017
DOI: 10.2174/1389557517666170120153930
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase: A Primary Target for Drugs and Insecticides

Abstract: The present review summarizes the current knowledge about acetylcholinesterase, its structure, function and biosynthesis, its inhibitors, and mode of action of inhibitors on it. Besides, the review also presents an overview about the resistance mechanism that the organisms develop due to the over-application of acetylcholinesterase inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 0 publications
1
46
1
1
Order By: Relevance
“…With respect to its termination of synaptic transmission, inhibition of AChE produces an excess accumulation of ACh and overstimulation of its receptors, causing uncoordinated neuromuscular function that often results in death due to respiratory paralysis [ 14 ]. As such, AChE inhibitors are widely used as pesticides [ 15 ] and anthelmintics [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to its termination of synaptic transmission, inhibition of AChE produces an excess accumulation of ACh and overstimulation of its receptors, causing uncoordinated neuromuscular function that often results in death due to respiratory paralysis [ 14 ]. As such, AChE inhibitors are widely used as pesticides [ 15 ] and anthelmintics [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acetylcholinesterase is a serine hydrolase that is vital for regulating the neurotransmitter acetylcholine in insects. This enzyme is an excellent molecular target for the development of insecticides [56,57]. The well-known active site has a deep and narrow gorge, with a catalytic site at the bottom and a peripheral site at the entrance.…”
Section: Discussionmentioning
confidence: 99%
“…Ion channels have a key role in maintaining normal CNS function. The channel hypothesis supports that ion channels constructed by Aβ on the nerve cell membrane allow abnormal flows of intracellular and extracellular ions, destroy the dynamic balance of ions and leads to nerve cell death (Thapa et al, 2017). Kem et al (1997) found that alkaloids in marine-derived larvae regulated ion channels.…”
Section: Ion Channel Regulatormentioning
confidence: 93%